Physicochemical water quality of Karabel, Çaltı, and Tohma brooks and blood biochemical parameters of Barbus plebejus fish: assessment of heavy metal concentrations for potential health risks - Demir, Tuğba; Mutlu, Ekrem; Aydın, Seyit; Gültepe, Nejdet (Springer Science and Business Media LLC, 2021)
The present study aims to comparatively examine the physical quality parameters of water samples taken from Karabel, Çaltı, and Tohma brooks in Sivas province and the blood biochemical parameters of blood samples of Barbus plebejus fish obtained from these waters. In periods when chemical pollution in water increased and decreased, it was determined that GLU and UA among blood biochemical parameters were significantly affected. Moreover, the potential risk levels of lead (Pb), copper (Cu), cadmium (Cd), and ferrous (Fe) for human health were compared to the international standards. Metal (Fe, Pb, Cu, and Cd) concentrations in the water were determined using atomic absorption spectrophotometer. The highest HQingestion values of Cd were found in Brook Çaltı, which were 0.0018 for adults and 0.1980 for children. THQ upper limit set by the United States Environment Protection Agency (USEPA) is < 1. It was determined that HQingestion, HQdermal, and THQ values of all the heavy metals were much lower than this limit. It was concluded that water quality parameters of samples taken from Karabel, Çaltı, and Tohma brooks on monthly basis for 12 months were not higher than the limits and the water qualities of brooks were determined to be "good".
Keywords: Adult; Cyprinidae; Risk Assessment; Metals, Heavy; Water Quality; Animals; Humans; Child; Water Pollutants, Chemical; Environmental Monitoring; 6. Clean water; 3. Good health; 13. Climate action; 14. Life underwater